المنطوق الغزواتي بين تنوع الأسلوب وتعدد الدلالة - بن عبد الواحد, محمد (University of Eloued جامعة الوادي, 2017)
يتّسم الكلام المنطوق- أحيانا- بطابع التضارب بينه وبين الأنظمة اللّغوية - أي القواعد - صوتية كانت أو صرفية أو تركيبية. والشائع بين النحاة أنّ الجملة اسمية أو فعلية، شرطها الإفادة ، كما تكون إسنادية أو غير إسنادية. ثم إنّ بنية التركيب تتكوّن – على أكثر تقدير- من ركن أساسيّ يمثّل النّواة، وهو عمدة عند النحاة العرب، ومن ركن آخر قد يستقيم الكلام بدونه ويأتي بفائدة إضافية للنّواة ويسمّى ملحقا أو فضلةً أو مكمّلاً، كما أنّ الإسناد قد يتعدّد. والترّكيب الإسنادي المثبت في المنطوق الغزواتي يلاحظ فيه تقدّم المسند إليه على المسند غالبا، مع توافقهما في النّوع والعدد. وتنوّع الأساليب في المنطوق الغزواتي كما هو الأمر في الفصحى مع بعض التّغييرات، وأهمّ هذه التّراكيب: الاستفهام والشّرط والتعجّب والاستثناء والتوكيد وأساليب المدح والذّم والإغراء والتحذير والاختصاص والإشارة والوصل والنّداء. وقد آثرت البحث في الجانب الترّكيبي للجملة الغزواتية وخصائصها لإبراز تلك القرابة الموجودة بين المنطوق المحلّي لسكان المنطقة والعربية الفصحى The spoken language is sometimes inconsistent with the linguistic systems, i.e. the phonetic, the morphological, or the syntactic rules. The grammarians say that the sentence can be either nominal or verbal provided that is meaningful, and it can also be referential or non-referential. The structure is essentially based on two parts: the nucleus which is considered by Arab grammarians as the fundamental part, and a complementary part that enhances this nucleus, but it doesn’t affect the spoken language. Studying the Gazaoueti dialect, we have observed that the predicate comes generally before the subject and they agree in gender and number. Like the Classical Arabic, the Gazaoueti dialect is characterized by the diversity of styles with some differences. The most important of these styles are: Interrogation, condition, exclamation, restriction, emphasis, praise, satire, exhortation, specialization, deictic devices. In this research we aimed at studying the morphological aspect of the Gazaoueti sentence and its features to show the relation between the Gazaoueti dialect and the Classical Arabic.
Keywords: الكلام المنطوق، المنطوق الغزواتي، الجملة الغزواتية; spoken language, Gazaoueti dialect, Gazaoueti sentence